Staphylococcus aureus leukocidin ED contributes to systemic infection by targeting neutrophils and promoting bacterial growth in vivo - Alonzo, Francis (2011)
Bloodstream infection with Staphylococcus aureus is common and can be fatal. However, virulence factors that contribute to lethality in S. aureus bloodstream infection are poorly defined. We discovered that LukED, a commonly overlooked leukotoxin, is critical for S. aureus bloodstream infection in mice. We also determined that LukED promotes S. aureus replication in vivo by directly killing phagocytes recruited to sites of hematogenously-seeded tissue. Furthermore, we established that murine neutrophils are the primary target of LukED, as the greater virulence of wild type S. aureus compared to a lukED mutant was abrogated by depleting neutrophils. The in vivo toxicity of LukED toward murine phagocytes is unique among S. aureus leukotoxins, implying its crucial role in pathogenesis. Moreover, the tropism of LukED for murine phagocytes highlights the utility of murine models to study LukED pathobiology, including development and testing of strategies to inhibit toxin activity and control bacterial infection.